OPTIMASI DISTRIBUSI BERAS DALAM PEMENUHAN PERSEDIAAN PANGAN DI PROVINSI PAPUA - Mustakim (Jurnal Media Akademik (JMA), 2024)
Papua Province has 8 (eight) districts and 1 (one) city with a population of around 1,019,247 people, around 106 districts, 53 sub-districts and 1,028 villages. Rice consumption is lower than other regions in a year, namely 78,890,131 kg or per capita per month 5.12 kg or per year 61.45 kg as evidenced by rice production in 2021 of 15,235,031 kg resulting in a deficit of local products and must be supported with supply from outside the city by importers. The reason for the low consumption per capita in Papua Province is the availability of rice, rising commodity prices for rice where people living in villages tend to have lower food security than people in cities because they are scattered. The purpose of this research is to analyze distribution route optimization so as to obtain minimum costs by using the Mixed Integer Linear Programming method by providing constrain capacity and flow conservation capacity limits. Model verification and validation as well as scenario creation from the initial model are expected to provide modeling in research. The type of data used in this research is quantitative and qualitative data. Rice supply comes from 104 farmers and 3 importers with 9 logistics producers, 9 collectors, 19 wholesalers, 17 agents and 9 distributors with 104 retail outlets. Data sources are primary data and secondary data. The data analysis technique used is observation. interview. and documentation. Analysis of the data using the analysis of the logistics distribution sector using descriptive analysis. The results of the study obtained an optimum cost of 9,779,678,000.00 or 56% of the total shipping costs in the field of Rp. 17,464,018,000.00 with a total distribution of rice from farmers 2,285.21 tons, importers 4,297.92 tons with total demand at retailers of 6,583 .12 tons with a total distribution route of 2 stages of 56 links, 3 stages of 35 links and 4 stages of 13 links with a link cost interval of Rp. 66.00 at the PC99 node up to 25,982.00 at the PC11 node